Spatial Distribution Of Andaliman Potential Habitat (Zanthoxylum acanthopodium DC.) in Samosir Island, North Sumatera - Siahaan, Lasriama; Hilwan, Iwan; Setiawan, Yudi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Andaliman breeding and regeneration (Zanthoxylum acanthopodium DC.) in its natural habitat tends to be slow and difficult. The purpose of this research was to determine the distribution pattern, spatial character, and potential suitable habitat for andaliman growth with a suitability model approach in Samosir island, North Sumatera. Andaliman distribution pattern based on the calculation of the Standard Morisita Index (Ip) shows various patterns. There are three categories of distribution pattern, depends on the Standard Morisita Index The distribution patterns on each plot based on the calculation are: random (Location 1 – open area (Ip = 0.00)), uniform (Location 2 – plantation forest (Ip = -0.77); Location 3 – open field (Ip = -0.09)), and clump (Location 4 – plantation forest (Ip = 0.36)). Analysis of habitat suitability for andaliman used spatial modelling with the Principal Component Analysis (PCA) approach. This method utilized ecological variables, i.e.: Bare Soil Index (BSI), slope, Digital Elevation Model (DEM), rainfall, Normalized Difference Moisture Index (NDMI), and Normalized Difference Vegetation Index (NDVI). The result is 69.8% of Samosir Island is suitable for andaliman, while 26.4% of it is considered as highly suitable habitat.